2020
DOI: 10.1021/acs.orglett.0c01950
|View full text |Cite
|
Sign up to set email alerts
|

Structural Design and Synthesis of Bimodal PNA That Simultaneously Binds Two Complementary DNAs To Form Fused Double Duplexes

Abstract: Bimodal PNAs are new PNA constructs designed to bind two different cDNA sequences synchronously to form double duplexes. They are synthesized on solid phase using sequential coupling and click reaction to introduce a second base in each monomer at Cα via alkyltriazole linker. The ternary bimodal PNA:DNA complexes show stability higher than that of individual duplexes. Bimodal PNAs are appropriate to create higher-order fused nucleic acid assemblies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 57 publications
(32 reference statements)
7
18
0
Order By: Relevance
“…PNA oligomers have been shown to inhibit transcription (antigene) and translation (antisense) of genes by tight binding to DNA or mRNA. 23,24 In this context, we have synthesized a novel class of PNA building blocks 13 and 14 (Scheme 2, vide infra) carrying the triazine-based Janus G−C nucleobase featuring orthogonally protected backbones, which could find application in developing PNAs useful for DNA/RNA interaction/ recognition studies. 25 The PNA building blocks 13 and 14 carrying an Fmoc Nterminus protecting group which are ready for PNA synthesis on the solid phase were obtained following the synthetic routes as given in Scheme 2 (vide infra).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…PNA oligomers have been shown to inhibit transcription (antigene) and translation (antisense) of genes by tight binding to DNA or mRNA. 23,24 In this context, we have synthesized a novel class of PNA building blocks 13 and 14 (Scheme 2, vide infra) carrying the triazine-based Janus G−C nucleobase featuring orthogonally protected backbones, which could find application in developing PNAs useful for DNA/RNA interaction/ recognition studies. 25 The PNA building blocks 13 and 14 carrying an Fmoc Nterminus protecting group which are ready for PNA synthesis on the solid phase were obtained following the synthetic routes as given in Scheme 2 (vide infra).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A new class of PNA termed bimodal PNA [Cγ(S/R)‐bm‐PNA] (Figure 6) was designed by Ganesh et al ., where a second nucleobase was added, attached via an amide bond to a side chain at Cγ of the aeg PNA backbone. [ 60–61 ] The Cγ‐bimodal PNA oligomers that had two nucleobases per aeg unit, were able to simultaneously bind two different complementary DNAs, forming duplexes from both the Cγ side and the tert ‐amide side while sharing a common PNA backbone. In addition, the ternary DNA1/Cγ(S/R)‐bm‐PNA/DNA2 complexes exhibited higher thermal stability when compared to their respective isolated duplexes.…”
Section: Modifications Of Pna: Improving Gene Targetingmentioning
confidence: 99%
“…In recent years, several double-headed nucleoside designs have been presented in the literature. [7][8][9][10][11][12][13] Our previous work has shown that depending on the site of attachment, the additional nucleobase can be positioned in the minor groove, [14][15][16][17] the major groove, [18][19][20] or the center of a DNA duplex. [21][22][23] In the latter case, given that the additional nucleobase is linked through a methylene to the 2'-position of 2'-deoxyuridine or arabinouridine (Figure 1, U X ), the doubleheaded nucleotide has been shown to behave as a condensed dinucleotide.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several double‐headed nucleoside designs have been presented in the literature [7–13] . Our previous work has shown that depending on the site of attachment, the additional nucleobase can be positioned in the minor groove, [14–17] the major groove, [18–20] or the center of a DNA duplex [21–23] .…”
Section: Introductionmentioning
confidence: 99%